THE THEORIZATION OF INSTITUTIONS OF JUDICIAL REVIEW OF THE CONSTITUTIONALITY OF LAWS - Titon Slamet Kurnia (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2014)
This article argues for judicial review of the constitutionality of legislation or laws. This article opines that the judiciary is more favourable in discharging the function as the guardian of the constitution than other government bodies. According to Marbury v. Madison, the judiciary enjoys the jurisdiction of judicial review to declare the unconstitutionality of legislation or laws because “it is emphatically the province and duty of the judicial department to say what the law is”. Artikel ini membahas tentang pengujian yudisial konstitusionalitas undang-undang. Dalam artikel ini penulis berpendapat bahwa badan yudisial merupakan kandidat utama sebagai penjaga konstitusi ketimbang badan-badan pemerintahan yang lain. Pendapat ini didasarkan pada kasus Marbury v. Madison yang meyakini bahwa menentukan makna hukum adalah ranah dan tugas badan yudisial, termasuk dalam melakukan pengujian yudisial untuk menyatakan suatu undang-undang inkonstitusional.